The Origin and Effect of the Nisi Prius Reports. - Newman, Paul (Journal of Legal History, 2024)
For some seventy years, rulings made by judges sitting at nisi prius were regularly reported, despite those reports being held in low esteem by the legal profession and such rulings being regarded as of little value as precedents. This article considers why those rulings, at least on matters of substantive law, were rejected as authorities, and sets out the reasons why they were nevertheless reported and cited. The article explains that the principal purposes of these reports were to introduce new members of the profession to the practicalities of preparing cases for trial, and to provide some authority, however slight, to cite in court. The article also explains that, while nisi prius rulings on substantive law were cited by nineteenth century judges, they were used differently to decisions of courts in banc. The greater authority of such rulings on points of evidence, at least up to the mid-nineteenth century, is also explored. The article concludes by examining the tendency of more recent judges to ascribe greater weight to nisi prius rulings than their nineteenth century counterparts, due to the modern profession's ignorance of the former difference in the treatment of nisi prius rulings and the decisions of courts in banc.